Meta Synthesis of GCG, SSB, and CSR on Islamic Banking Performance - Usdeldi Usdeldi; M. Ridlwan Nasir; Muhamad Ahsan (Ekonomi Syariah IAIN Kudus, 2021)
This research applies a meta-synthesis of research articles on financial and maqasid sharia performance from three dimensions: Good Corporate Governance (GCG), Sharia Supervisory Board (SSB), and Corporate Social Responsibility (CSR). The meta-synthesis was carried out on 50 articles from Scopus-indexed international (Q4-Q1) and Sinta-accredited national (S5-S1) journals published between 2000 and 2020. The meta-synthesis is used as a qualitative systematic review method, which has not been used in similar studies. The results show an inconsistent influence of exogenous variables (GCG, SSB, and CSR) on endogenous variables (financial performance and maqasid sharia performance). The inconsistency is likely due to differences in various and incomprehensive uses of variables and measurement indicators. The optimal implementation of GCG, SSB, and CSR can affect financial performance.